Primary cutaneous cryptococcosis in an eight-year-old immunocompetent child: how to treat? - Lenz, D.; Held, Jürgen; Goerke, S.; Wagner, Dirk; Tintelnot, K.; Henneke, P.; Hufnagel, M. (Klinische Pädiatrie, 2015)
Here we report on a case of primary cryptococcal skin infection in an immunocompetent 8-year-old boy. The infection first manifested itself as a subcutaneous abscess around the proximal joint of his right thumb after a minor injury from contact with a thorny shrub. After surgical incision and drainage was performed, Cryptococcus neoformans var. neoformans was the only pathogen cultured from the lesion. An agglutination test for the capsular antigen in serum displayed negative results and the immunological work-up revealed no underlying immunodeficiency. A "watch and wait" strategy - one without systemic antifungal treatment - was adopted and this resulted in uneventful healing. In summary, primary cryptococcal skin infections in immunocompetent hosts may be managed successfully by surgical treatment in combination with careful clinical follow-up. This approach may help avoid unnecessary antimicrobial treatments.
EVALuna2:7712